PENGARUH INFORMATION ASYMMETRY, FIRM SIZE, DAN LEVERAGE TERHADAP MANAJEMEN LABA - Fitri Aamalia Al Thaaf; Agus Munandar (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study was required with the intention of achieve empirical evidence concerning the Influence of Information Asymmetry, Firm Size, also Leverage on Earnings Management. Sample collection method worn in this study was purposive sampling. Population used in this study are companies in the real estate, property, and building construction sector that are listed on the Indonesia Stock Exchange in 2019-2021 and have published their company's financial statements. Sample for this study is 30 companies over a three periods, making a total sample of 90 data. Based on the yields of the partial test (t test) it shows that information asymmetry (SPREAD) and company size (SIZE) have no significant influence on earnings management. While leverage (DER) has a significant impact on earnings management. So it can be inferenced from the analysis and discussion that information asymmetry has a positive and no significant influence on earnings management, company size has a negative and no significant impact on earnings management, and leverage has a positive and significant impact on earnings management